Technology distribution channels understanding and managing channels to market - Dent, Julian (Kogan Page, 2014)
"Using numerous examples from global technology corporations, Technology Distribution Channels explores the chain that makes products and services available for market and explains how to make the most of each step of the process. By defining the role and significance of the various partners involved, including distributors, wholesalers, and final-tier channel players, the text provides a clear understanding of the entire go-to-market process, while also explaining channel partners' business models and how to engage with them for effective market access.Technology Distribution Channels covers both the tactical and strategic dimensions of channel economics and includes information on accessing and servicing markets and customers, controlling brands, integrating web and online channels, building the value proposition and creating differentiation. Comprehensive and clear, this book provides the knowledge needed to improve business models to ensure maximum market exposure and successful product delivery"--